Efficacy and safety of total glucosides of paeony in the treatment of recurrent aphthous ulcers: a systematic review and meta-analysis - Liu, Zijian; Liu, Xingyun; Han, Yangping; Wang, Yutian; Guo, Qianyun; Lu, Mingxing; Li, Shufang; Han, Ying; Liu, Hongwei (Frontiers in Pharmacology, 2024)
Background Recurrent aphthous ulcer (RAU) had high prevalence and lacked widely recognized treatment. Total glucosides of paeony (TGP) was used in the treatment of RAU in recent years. This study was to summarize the efficacy and safety of TGP in the treatment of RAU. Methods We searched eight commonly used databases for relevant studies that published before November 1, 2023. Primary outcome was visual analogue scale (VAS). Secondary outcomes included overall response rate, significant response rate, ulcer healing time, interval, number of ulcers, and serum inflammatory factors. We conducted the meta-analysis, assessed risk of bias and the confidence of the evidence, by using Stata 15.0, Review Manager 5.4, and Gradepro. Results Nine randomized controlled trials (RCTs) encompassing 883 patients with RAU were included in the final analysis. the VAS in the TGP group was lower than that in the control group (MD = -1.18, 95% CI = -1.58 to -0.78, p < 0.001, moderate-certainty evidence), subgroup analysis suggested longer (>8 weeks) medication and observation led to a more significant reduction in pain (p = 0.02). Moreover, TGP had higher overall response rate (RR = 1.18, 95% CI = 1.04 to 1.33, p = 0.008, very low-certainty evidence) and significant response rate (RR = 1.72, 95% CI = 1.38 to 2.14, p < 0.001, very low-certainty evidence), accelerated ulcer healing (MD = -1.79, 95% CI = -2.67 to -0.91, p < 0.001, low-certainty evidence), and extended intervals (MD = 23.60, 95% CI = 14.17 to 33.03, p < 0.001, very low-certainty evidence). The efficacy of TGP in reducing the number of ulcers showed no significant difference compared to the control group (MD = -1.66, 95% CI = -3.60 to 0.28, p = 0.09, low-certainty evidence). Moreover, TGP treatment was associated with a higher incidence of abdominal symptoms (RR = 3.27, 95% CI = 1.62 to 6.60, p < 0.001). Conclusion TGP appears to hold promise as a widely-used clinical therapeutic option for treating RAU. Nevertheless, further rigorous studies of high quality are required to validate its effectiveness.